The impact of innovation on firm performance in the Malaysian batik industry - Ismail, Normaz Wana; Mohamad Akhir, Noor Haslina; Kaliappan, Shivee Ranjanee; Said, Rusmawati (Inderscience, 2019)
This paper aims to explore the extent of innovation in the Malaysian batik industry and to analyse the impact of innovation on the batik firm's performance. The evolution in the batik industry has brought various innovations to the batik making process, batik products, as well as the marketing and organisational methods. However, some of the batik entrepreneurs maintain the traditional approaches and managed manually. Using face-to-face interview surveys in Kelantan and Terengganu, we found that batik entrepreneurs in the sample have taken some initiatives to undertake innovations, especially in the marketing and batik making process. Results from empirical analysis revealed that only product innovation has a significant impact on batik firm's performance. This study offer a new finding for the idea of incorporate all four types of Schumpeterian innovations to analyse its impact on firm performance in batik industry.